PILKADA SERENTAK, EKSKLUSI PARTAI POLITIK, DAN MASA DEPAN POLITIK REPRESENTASI - Caroline Paskarina (Magister Ilmu Politik Universitas Hasanuddin, 2016)
Since the beginning of its implementation, direct local election has brought great expectation to perform radical changes in fulfilling the political rights of public to determine local political leader in their region. This expectation gained momentum from the contestation of national versus local political discourse, that created direct local election as new field of discursively to build local political power. Meanwhile, various researches on direct local election have found that the high expectation of political freedom actually had been 'hijacked' by political oligarchy that made direct local elections very expensive event, but could not be guaranteed to increase public welfare. The concurrent local elections, which will be held for the first time at the end of year 2015, become new field of discursively to overcome the public apathy. This paper positions concurrent local elections as discursive struggle that established figure-based politics as hegemonic discourse and at the same time, excluded political parties within the discourse, through the dislocations of meaning, that define simultaneity as instrumental arrangement. The exclusion of political parties is also dislocated because this involvement is understood only as 'political vehicle' or formalistic institution for candidacy. These dislocated meanings evoked a question, whether concurrent local elections could create new form of political representation, or in fact, establish figure-based politics hegemony that actually challenge democratization.